Microfabrication of a gadolinium-derived solid-state sensor for thermal neutrons - Pfeifer, Kent B. (J Radiat Res, 2017)
Neutron sensing is critical in civilian and military applications. Conventional neutron sensors are limited by size, weight, cost, portability and helium supply. Here the microfabrication of gadolinium (Gd) conversion material–based heterojunction diodes for detecting thermal neutrons using electrical signals produced by internal conversion electrons (ICEs) is described. Films with negligible stress were produced at the tensile-compressive crossover point, enabling Gd coatings of any desired thickness by controlling the radiofrequency sputtering power and using the zero-point near p(Ar) of 50 mTorr at 100 W. Post-deposition Gd oxidation–induced spallation was eliminated by growing a residual stress-free 50 nm neodymium-doped aluminum cap layer atop Gd. The resultant coatings were stable for at least 6 years, demonstrating excellent stability and product shelf-life. Depositing Gd directly on the diode surface eliminated the air gap, leading to a 200-fold increase in electron capture efficiency and facilitating monolithic microfabrication. The conversion electron spectrum was dominated by ICEs with energies of 72, 132 and 174 keV. Results are reported for neutron reflection and moderation by polyethylene for enhanced sensitivity, and γ- and X-ray elimination for improved specificity. The optimal Gd thickness was 10.4 μm for a 300 μm-thick partially depleted diode of 300 mm(2) active surface area. Fast detection (within 10 min) at a neutron source-to-diode distance of 11.7 cm was achieved with this configuration. All ICE energies along with γ-ray and K(α,β) X-rays were modeled to emphasize correlations between experiment and theory. Semi-conductor thermal neutron detectors offer advantages for field-sensing of radioactive neutron sources.